CICERÓN, EPIGRAMA 1 SOUBIRAN: CUESTIONES DE ATRIBUCIÓN E INTERPRETACIÓN HISTÓRICA Y LINGÜÍSTICA - M. Morelli, Alfredo (Myrtia, 2003)
This epigram and the other two extant ones ascribed to Cicero can be seen as representative of the typical Roman epigrammatic taste in the age of the late Republic. Mittere in the first verse is to be interpreted as a technical term used in land-surveying: 'to draw (or to mark) the boundary line, to delimit'. The whole epigram would indicate a derisive metatio of the small estate of Vetto, whose extent can be covered by a sling throw, if not even an unsuccessfid one, as the stone falls from the sling-pouch and lands by the slinger's feet. Like the other two, this epigram can also be attributed to Cicero, although some doubts still remain, concerning prosody of final short -o of Vetto (not attested, but not impossible in the age of Cicero) and especially a couple of idiomatic peculiarities which are found also in Ovid.